Diets and weight clearing the confusion - Learning seed (Lake Zurich, Ill. : Learning Seed, 1999)
Discusses common myths about weight and diet, provides guidelines on obesity and optimal weight, and explains the relationship between physical activity and weight control
myth 1. Fat makes you fat - myth 2. Diet to lost weight - myth 3. Thin is natural - myth 4. Obesity is about weight - myth 5. It's all in the genes - myth 6. Good food / Bad food - myth 7. Food controls weight
Title from title screen
Narrator, Matthew Lenhart
DVD Format
Keywords: Diet; Body weight -- Regulation; Reducing diets